Corporate Social Responsibility HSBC Case Study: Ciwidey Pintar - Putridita, Bunga Mentari; Rudito, Bambang (Journal of Business and Management, 2014)
Indonesia is the biggest country in Southeast Asia, unfortunately It has not been able to be the representative for other countries in the economy and education sector, it also fails to have the prosperity which is evenly distributed for all society. Therefore, Indonesia is still categorized as developing country. This not-well-distributed prosperity creates any gap in social life for example there are still many children who live in remote area cannot get the access of having the education as they should be. To remove the gap, the numerous programs have been arranged by the government, one of them is the supervision to the social program of the company. At this final assignment project, the author wants to evaluate Ciwidey Pintar program which is Corporate Social Responsibility program of HSBC Bank. It aims to bear future generations through formal and informal education and answer the problem explained above.The objective of this final assignment is to know more deeply about the program of the society development of HSBC called Ciwidey Pintar. In addition, it aims to analyze the impacts of whether the target is achieved or not. The author will analyze the relationship among the involved parties in holding the program to get success result. To achieve the objectives above, the author uses some theories such community development, corporate social responsibility, program ofsociety empowerment, and sustained business theories. Besides, to get the project result, the author uses a research methodology; design of problem identifications; data collection; data analysis; and the conclusion. The result is Ciwidey Pintar. It has given a big contribution in developing education in one of the remote areas; also it brings the success of the internal part of the company for the employee’s participation at this program. The problem is only about the program activity that totally does not show the empowerment spirit. For the first recommendation, they need to focus on two program impacts, social and environment. The program is adjusted with the environment condition to make use of its society.Keywords: corporate social resposibility, ciwidey pintar, community empowerment, case study.